DNA barcode shows discordant cases among morphological and molecular species identification in Isbrueckerichthys (Siluriformes: Loricariidae) - de Almeida, Rafael B. (2024)
Isbrueckerichthys is a genus of armored catfish (Siluriformes: Loricariidae) with five species in the lowlands from the Ribeira de Iguape basin and in the uplands of the Tibagi River basin. Despite the validation of the morphological species, molecular data to investigate gene flow and species delimitation have not been completed for all species. For this purpose, we compared sequences of COI region associated with barcoding molecular identification, aiming for a species delimitation analysis and generating population data of I. alipionis, I. epakmos, I. duseni, I. cf. duseni, I. saxicola, and I. calvus. The K2P genetic distance, molecular species delimitation analysis, and well-sustained branches in the phylogenetic tree validate I. alipionis, I. epakmos, and I. duseni, and suggest I. cf. duseni as a valid molecular operational taxonomic unit. However, no differences were detected between I. saxicola and I. calvus. The discordance between molecular and morphological species may be due to the recent dispersal of some Isbrueckerichthys representatives at the border between the Ribeira de Iguape and Tibagi basins. The isolation features of the mountainous region of Ribeira de Iguape basin and headwaters captures to uplands are presented to explain the dispersion and the cases of incipient speciation in Isbrueckerichthys lineages.